'Time to ride the monster train': multiplicity, the Midnighter and the threat to hegemonic superhero masculinity. Issue 5 (3rd September 2017) - Camp, Lisa D.
ABSTRACT: This article is concerned with how and why a figure such as DC's Midnighter might be able both to enact the current discourse of ideal masculinity and humanity in comic books, and to usurp that discourse in order to generate new understandings which grapple with the ever-imminent realities of posthuman cyborg bodies and openly lived LGBTQIA+ experiences in a way that does not merely dismiss them as sub human. It utilises posthumanism, monster theory, queer theory, feminist criticism, and 'body' theory in an analysis of the Midnighter in his New 52 run under DC, in order to take a critical look at the multiplicity of the Midnighter's identity to identify what makes him into such 'a rare and violent snowflake', and to demonstrate humanity's embedded monstrosity.